RADEC: INDONESIAN-BASED LEARNING MODEL IN IMPROVING STUDENTS' UNDERSTANDING OF NARRATIVE MATERIALS AT MAN 5 JOMBANG (BEST PRACTICE) - Kiswati; Vicky Galih Dewangga; Moh. Rodli; Hari Prastyo (LPPM Universitas PGRI Jombang, 2025)
Grammar is one of the important components of English but many students find it difficult to understand it, including students of MAN 5 Jombang. The researcher conducted a study by implementing the RADEC learning model (Read, Answer, Discuss, Evaluate, Create) which aims to improve the understanding of